Martial law and the Philippine economy - Emmanuel S. De Dios; Maria Socorro Gochoco-Bautista; Jan Carlo Punongbayan (University of the Philippines, School of Economics (UPSE), 2021)
Part of a proposed anthology, this article provides a concise review of the economic performance during the period of the Marcos dictatorship (1972-1985) from a comparative historical perspective. We examine the external events and internal policy responses that made possible the high growth in the early years of martial law and show that these are integral to explaining the decline and ultimate collapse of the economy in 1984-1985. The macroeconomic, trade, and debt policies pursued by the Marcos regime-particularly its failure to shift the country onto a sustainable growth path-are explained in the context of the regime's larger political-economic programme of holding on to power and seeking rents.
Keywords: N15; O53; P48; 330; martial law; Philippine economy; economic history; political economy